Parameter identification in a structured population model. (21st August 2019) - Lorz, Alexander; Pietschmann, Jan-Frederik; Schlottbom, Matthias
Abstract: We study parameter identification problems in a structured population model without mutations. Given measurements of the total population size or critical points of the population, we aim to recover its growth rate, death rate or initial distribution. We present uniqueness results under suitable assumptions and present counterexamples when these assumptions are violated. Our results are supplemented by numerical studies, either based on Tikhonov regularization or the use of explicit reconstruction formulas.